Measuring Vulnerability to Anxiety: Factorial Structure, Reliability, Validity, and Discriminatory Accuracy of the Anxiety Sensitivity Index–3–PT. (2nd October 2019) - Ganho-Ávila, Ana; Moura-Ramos, Mariana; Gonçalves, Óscar F.; Almeida, Jorge
Abstract: We evaluated the Portuguese version of the Anxiety Sensitivity Index 3 (ASI–3–PT). Results of a confirmatory factor analysis ( N = 603; 65.3% women, M age = 28.55, SD = 10.42) confirmed multidimensionality of the construct and the receiver operating characteristic confirmed the discriminant capacity of the measure between clinical and nonclinical samples.